One-dimensional Bose gases on an atom chip - Ferreras, Jorge (2018)
Ultracold atomic gases have proven to be an excellent tool for research in quantum systems. A Bose gas can be trapped on an atom chip using very well defined and tunable spatially-dependent potentials. The proximity of the atoms to the chip permits the use of low currents allowing for highly accurate temporal changes.